A Stage-Specific OTX2 Regulatory Network and Maturation-Associated Gene Programs Are Inherent Barriers to RPE Neural Competency - Tangeman, Jared A.; Pérez-Estrada, J. Raúl; Van Zeeland, Emily; Liu, Lin; Danciutiu, Alexandra; Grajales-Esquivel, Erika; Smucker, Byran; Liang, Chun; Del Rio-Tsonis, Katia (Frontiers in Cell and Developmental Biology, 2022)
The retinal pigment epithelium (RPE) exhibits a diverse range of plasticity across vertebrates and is a potential source of cells for the regeneration of retinal neurons. Embryonic amniotes possess a transitory ability to regenerate neural retina through the reprogramming of RPE cells in an FGF-dependent manner. Chicken RPE can regenerate neural retina at embryonic day 4 (E4), but RPE neural competence is lost by embryonic day 5 (E5). To identify mechanisms that underlie loss of regenerative competence, we performed RNA and ATAC sequencing using E4 and E5 chicken RPE, as well as at both stages following retinectomy and FGF2 treatment. We find that genes associated with neural retina fate remain FGF2-inducible in the non-regenerative E5 RPE. Coinciding with fate restriction, RPE cells stably exit the cell cycle and dampen the expression of cell cycle progression genes normally expressed during regeneration, including E2F1. E5 RPE exhibits progressive activation of gene pathways associated with mature function independently of retinectomy or FGF2 treatment, including retinal metabolism, pigmentation synthesis, and ion transport. Moreover, the E5 RPE fails to efficiently repress OTX2 expression in response to FGF2. Predicted OTX2 binding motifs undergo robust accessibility increases in E5 RPE, many of which coincide with putative regulatory elements for genes known to facilitate RPE differentiation and maturation. Together, these results uncover widespread alterations in gene regulation that culminate in the loss of RPE neural competence and implicate OTX2 as a key determinant in solidifying the RPE fate. These results yield valuable insight to the basis of RPE lineage restriction during early development and will be of importance in understanding the varying capacities for RPE-derived retinal regeneration observed among vertebrates.